The Informal Sector in Urban Economy : Low Income Housing in Lahore - Alvi, Imtiaz (Karachi Oxford University Press, 1997)
Lack of housing for the poor is one of the most formidable problems that developing nations face today. This book seeks to clarify the scope and limitation of self-help housing - both as a concept and as a practice - and to contribute to the state of knowledge by presenting a case study of Lahore.
Include Bibliography and Index
Keywords: Pakistan--Lahore -- Housing policy